Convertible securities in merger transactions - Finnerty, John D.; Jiao, Jie; Yan, An (Journal of Banking & Finance, 2012)
This paper provides a rationale for the use of convertible securities as the medium of exchange in corporate change-of-control transactions. We argue that convertible securities can resolve the information asymmetry about the bidder’s value while at the same time mitigating the information asymmetry about the target’s value. In contrast, deals with cash or stock can only address one information asymmetry or the other but not both. Empirically, we find that a bidder is more likely to offer convertible securities, rather than all cash or all stock, when both the bidder and its target face large asymmetric information problems. We also find that both bidders and targets in convertible deals enjoy positive abnormal stock returns around takeover announcements. These findings provide empirical support for the use of convertible securities to resolve the double-sided asymmetric information problem. Finally, we find that bidder returns in convertible deals are larger than in all-cash and all-stock deals, but that target returns in convertible deals are smaller than in all-cash and all-stock deals.